Geodynamic evolution of the SW Europe Variscides - Ribeiro, António (2007)
Abstract The early evolution of SW Europe Variscides started by opening of the Rheic ocean at 500 Ma, splitting Avalonia from Armorica/Iberia. Subduction on the SE side of Rheic generated the Paleotethys back-arc basin (430–390 Ma, splitting Armorica from Iberia), with development of Porto-Tomar-Ferreira do Alentejo (PTFA) dextral transform defining the boundary between continental Armorica and Finisterra microplate to the W. Obduction of Paleotethys was followed by Armorica/Iberia collision and emplacement of NW Iberian Allochthonous Units at 390–370 Ma, whereas toward the west of PTFA, there was antithetic ophiolite obduction (Beja-Acebuches and Rheic ophiolites plus Finisterra continental slices) on top of Ossa-Morena Zone, with simultaneous development of eclogites and orogenic magmatism under a flake–double wedge tectonic regime. Continued convergence (<370 Ma) proceeded by intracontinental deformation, with progressive tightening of the Ibero-Armorican Arc through dextral transpression on the Cantabrian Indentor, from Iberia to Armorica. The proposed model is discussed at the light of the driving mechanism of ‘‘soft plate tectonics.’’